Evaluation of a group format of clinician-guided, parent-delivered cognitive behavioural therapy for child anxiety in routine clinical practice: a pilot-implementation study - Evans, R; Hill, C; O'Brien, D; Creswell, C (Wiley, 2018)
Background Randomised controlled trials suggest that cognitive behavioural therapy (CBT) delivered by parents who are guided, in groups, by clinicians (Group GPD‐CBT) is an efficacious and potentially efficient treatment approach for child anxiety. The extent to which these results translate to routine settings is unclear. We evaluated Group GPD‐CBT as delivered in UK routine clinical services.